Optimization of Dimsum Production Profits Using the Branch and Bound Method - Andini, Qonita Putri; Husein, Ismail (Sinkron : jurnal dan penelitian teknik informatika, 2024)
The dimsum industry in Indonesia is currently experiencing very significant development, because many businesses offer processed dimsum products for convenient consumption. The characteristics of dimsum are varied and suitable to be served as a snack. This has created an increasing number of dimsum enthusiasts, seen from the emergence of restaurants serving dimsum menus originating from China. The aim of this research is to determine the maximum profit achieved in making dimsum using the Branch and Bound technique. Using the branch and bound method because it is a mathematical model which is a development of a linear program, where all decision variables must be integers, this method limits the optimal solution to a whole by creating an upper and lower branch for each solution which has a fractional value. to be a round value so that each restriction will produce a new branch. Based on the research results, it can be concluded that the optimal production level using the Branch And Bound method is IDR 19,054,950 per month. When compared with the profits before using the Branch and Bound method, the profits obtained were IDR 18,800,000. This shows that by using the Branch and Bound method, the profit of the Mikaila Bakery cake shop increases by IDR. 1.3% or around Rp. 254,950 per month. Sensitivity analysis shows that profits will remain at optimal conditions if changes in the objective function coefficients are less than or equal to the objective function coefficients in the initial model.